Immediate full-arch rehabilitation of the severely atrophic maxilla supported by zygomatic implants: a prospective clinical study with minimum follow-up of 6 years. Issue 12 (December 2017) - Agliardi, E.L.; Romeo, D.; Panigatti, S.; de Araújo Nobre, M.; Maló, P.
Abstract: The aim of this study was to evaluate the outcomes of immediate full-arch prostheses supported by zygomatic implants alone or in combination with standard fixtures after a minimum of 6 years of loading. From October 2008 to April 2010, 15 patients with severely atrophic maxillae were treated using four zygomatic implants or two zygomatic implants in conjunction with two conventional fixtures. All subjects received a fixed screw-retained prosthesis within 3 hours of surgery, while the final restoration was delivered after 6 months. Follow-up examinations were scheduled to evaluate zygomatic implant survival, conventional dental implant success, prosthetic success, plaque and bleeding scores, marginal bone loss for conventional dental implants, and patient satisfaction. Forty-two zygomatic fixtures and 18 standard implants were placed. Patients were followed up for a minimum of 79 months (range 79–97 months, average 90.61 months). No implant was lost, leading to implant and prosthetic survival rates of 100%. Bone loss for conventional implants averaged 1.39 ± 0.10 mm after 6 years of function, leading to a 100% implant success rate. High levels of patient satisfaction were recorded. These medium-term results indicate that immediate full-arch rehabilitation supported by zygomatic implants could be considered a viable treatment modality for the severely atrophic maxilla.